The good, the bad, and the ugly: Esping-Andersen's regime typology and the religious roots of the Western welfare state - Philip Manow (Max Planck Institute for the Study of Societies, 2004)
Esping-Andersen's 'Three World of Welfare Capitalism' has been the most influential contribution of recent years to the comparative welfare state research literature. According to Esping-Andersen, the welfare state basically comes in three variants: as a social-democratic, a conservative, or as a liberal regime. Yet, at a closer look particularly the conservative regime type proves to be a highly problematic category. The article claims that major problems of the 'three worlds'-typology originate from Esping-Andersen's sole focus on the class conflict, whereas he only very selectively accounts for the importance of religious cleavages. Major empirical problems of his approach vanish once we take into account not only the impact of the Catholic social doctrine on the development of the welfare state, but consider also the influence of social Protestantism, especially that of reformed, 'free', disestablished or dissenting Protestantism. The paper substantiates this claim with data-analysis for the early formative period of welfare state formation (1890-1920) and for its times of growth and crisis (1960s-1990). – – Folgt man dem einflussreichsten Beitrag zur vergleichenden Wohlfahrtsstaatsforschung der letzten Zeit, Esping-Andersens 'Three Worlds of Welfare Capitalism', so tritt der entwickelte westliche Sozialstaat in drei Varianten auf: entweder als sozialdemokratisches, oder als konservatives, oder als liberales Wohlfahrtsstaatsregime. Ein genauerer Blick zeigt jedoch, dass Esping-Andersens Typenbildung und Länderzuordnungen insbesondere im Fall des konservativen Regimes problematisch sind. In diesem Papier argumentiere ich, dass gravierende Probleme daherrühren, dass seine Theorie vornehmlich den Klassenkonflikt, nur sehr selektiv aber den Einfluss konfessioneller Faktoren in den Blick nimmt. Wesentliche empirische Unstimmigkeiten seines Ansatzes lassen sich lösen, wenn man neben der Bedeutung der katholischen Soziallehre für den institutionellen Entwicklungspfad des entwickelten Wohlfahrtsstaates auch den Einfluss des Protestantismus, und hier insbesondere den Einfluss der reformierten protestantischen Strömungen, in den Blick nimmt. Der Beitrag zeigt dies mit vergleichenden Daten sowohl für die Frühphase (1890-1920) als auch für die Hochzeit des entwickelten Wohlfahrtsstaats (1960-1990).
Keywords: 300